Pengembangan Model Pembelajaran Berbasis Inkuiri-Transaksional untuk Pendidikan Agama Islam Aspek Sejarah pada Sekolah Menengah Kejuruan - Khoirawati - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
The purpose of this study was to develop an instructional materials model of the world history of Islam religion for Vocational High School. This study employed a research and development method. The instructional materials developed based on inquiry-trans- actional approach, The eld research was conducted at SMK Pagar Alam City-South Su- matra province, involving of 11 experts, 53 Vocational High School students, 3 Vocational High School teachers and, 2 educational of cers. The results of the study were: (1) a con- ceptual model of instruction of the world history of Islam religion; (2) a procedural model of instructional design for developing instructional materials; (3) a set of instructional materials model of the world history of Islam religion, consisted of printed, interactive Compact Disc (CD), teachers guide, and teaching aids.